A preliminary thermal comfort study in tropical buildings Located in Malaysia - Yau, Y.H. (2008)
A preliminary study of the thermal comfort level in several buildings at University of Malaya is presented in this paper. For the study, a subjective field survey study was conducted on thermal comfort at buildings in University of Malaya. The study is based on the analysis of 141 sets of questionnaires compiled from field survey study in nine buildings located at the University. The results of the subjective and objective data are then compared to the results acquired from the ASHRAE thermal comfort tool. This research found that most of the buildings fail to provide a thermally comfort environment to the occupants. Based on the results of the thermal comfort study, the existing old HVAC systems installed in the buildings are recommended to be retrofitted or replaced for achieving minimum thermal comfort level per ASHRAE recommendation (ANSI/ASHRAE Std 55, 2004).